Influence of Microfinance Trainers’ Characteristics on Women’s Acquisition of Financial Skills: A Case of Women’s Self-Help Groups in Kiambu County, Kenya - Mwaniki, Tabitha Wawira; Wamue-Ngare, Prof. Grace; Okemwa, Dr. Pacificah (International Journal for Innovation Education and Research, 2018)
Microfinance institutions have had their fair share of challenges, especially the ability of the women entrepreneurs to manage loans secured from the institutions. Thus, the study intended to examine the effectiveness of microfinance trainers’ characteristics on women’s acquisition of financial skills in Kiambu County, Kenya. The study was guided by Pearson’s Theory of Gender Relations, The Endogenous Growth and Knowledge-Based Theories. It adopted mixed methods approach and thus applied exploratory research design. The target population comprised of 8 Credit Officers, 25 staff members, 1900 women in SHGs, 700 spouses and 100 Key Informants (Training Officers) all totaling to 2733. Using the Central Limit Theorem to obtain a sample of MFIs, that is, 25.0% of 8 MFIs and 295 respondents, that is, 10.9% of 2708, were selected. Purposive sampling was used to select two Credit Officers and 20 key informants (Training Officers). 190 women in SHGs and 83 spouses were selected using simple random sampling. Focus group discussions were used to collect data from women in SHGs and their spouses, interview schedules for women in SHGs, Credit Officers and spouses whereas questionnaires were used to gather information from Training Officers. Qualitative data was analyzed thematically along the study objectives and presented in narrative forms while the quantitative data was analyzed descriptively using frequencies and percentages with the help of Statistical Packages for Social Science (SPSS 23) and were presented using tables and charts. The study established that microfinance trainers’ characteristics influence women’s acquisition of financial skills. Thus, the study recommends that microfinance trainers’ need to update their skills to match the changing times such as adopting use of ICT and attitude change towards women empowerment. The trainers need to plan for quarterly and semi-annual evaluation of training programmes since they are effective in ascertaining of the efficacy of such programmes.